Fatigue and rapid hamstring/quadriceps force capacity in professional soccer players - Greco, Camila C. [UNESP]; Da Silva, Wendell L. [UNESP]; Camarda, Sérgio R.A. [UNESP]; Denadai, Benedito S. [UNESP] (Wiley, 2013)
The aim of this study was to investigate the effect of fatigue induced by an exhaustive laboratory-based soccer-specific exercise on different hamstrings/quadriceps (H:Q) ratios of soccer players. Twenty-two male professional soccer players (23·1 ± 3·4 year) performed maximal eccentric (ecc) and concentric (con) contractions for knee extensors (KE) and flexors (KF) at 60° s-1 and 180° s-1 to assess conventional (Hcon:Qcon) and functional (Hecc:Qcon) ratios. Additionally, they performed maximal voluntary isometric contraction for KE and KF, from which the maximal muscle strength, rate of force development (RFD) and RFD H:Q strength ratio (RFDH:Q) were extracted. Thereafter, subjects were performed an exhaustive laboratory-based soccer-specific exercise and a posttest similar to the pretest. There was significant reduction in Hcon:Qcon (0·60 ± 0·06 versus 0·58 ± 0·06, P<0·05) and in Hecc:Qcon (1·29 ± 0·2 versus 1·16 ± 0·2, P<0·01) after the soccer-specific exercise. However, no significant difference between Pre and Post exercise conditions was found for RFDH:Q at 0-50 (0·53 ± 0·23 versus 0·57 ± 0·24, P>0·05) and 0-100 ms (0·53 ± 0·17 versus 0·55 ± 0·17, P>0·05). In conclusion, H:Q strength ratios based on peak force values are more affected by fatigue than RFDH:Q obtained during early contraction phase. Thus, fatigue induced by soccer-specific intermittent protocol seems not reduce the potential for knee joint stabilization during the initial phase of voluntary muscle contraction. copy; 2012 Scandinavian Society of Clinical Physiology and Nuclear Medicine.
Keywords: Injury; Isokinetic; Power; Strength; Torque; adult; athlete; exercise; exhaustion; fatigue; hamstring; human; human experiment; isokinetic exercise; knee function; laboratory; male; muscle isometric contraction; muscle strength; normal human; priority journal; quadriceps femoris muscle; torque; Adult; Analysis of Variance; Biomechanics; Exercise Test; Humans; Isometric Contraction; Knee Joint; Male; Muscle Fatigue; Muscle Strength; Physical Endurance; Quadriceps Muscle; Range of Motion, Articular; Soccer; Time Factors; Young Adult